Analyzing the Effectiveness of the Turba (Turun Bareng) Strategy for Student Recruitment in the Era of Social Media Exclusivity - Febi Febrianto; Moh. Rofik; Uryatul Hikmah; Muthia Hasanah; Muh. Kamil; M. Kholilur Rohman; Akmal Mundiri (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the effectiveness of the Turba (Turun Bareng) strategy in recruiting prospective students in the era of social media exclusivity at MA Raudlatul Jinan. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving the principal, public relations officers, admission committee members, teachers, parents, prospective students, and community leaders. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal three major aspects of the Turba strategy's effectiveness. First, Turba successfully builds trust among prospective students and parents through direct interpersonal communication. Second, Turba serves as an effective personal communication approach that reaches communities beyond the limitations of social media, particularly those with varying levels of digital access and literacy. Third, Turba significantly contributes to increasing new student enrollment by transforming public trust into actual enrollment decisions. The study concludes that despite the widespread use of digital marketing in educational institutions, interpersonal communication remains a fundamental component of effective student recruitment. Integrating face-to-face engagement with digital promotion enables educational institutions to establish stronger public trust, broaden community outreach, and enhance enrollment outcomes.